Awareness and Knowledge of E-learning resources among Undergraduate Medical Students - FARRUKH SARFRAZ; HARRISON DAKA; KABUNGA NACHIYUNDE; FAHAD SARFRAZ; SEHRISH LIAQAT (Pakistan Journal of Medical & Health Sciences, 2024)
Purpose: Teaching and learning have evolved significantly in recent decades, with e-learning emerging as a recent development. Factors driving its growth include student needs, cost reduction, quality improvement, and accessibility. As geographical dispersion increases, e-learning adoption is likely to expand. To assess the level of awareness among medical students about e-learning resources. Material and Methods: A cross-sectional study was conducted at Azra Naheed Medical College, Superior University Lahore, involving a sample of 262 participants. Following obtaining informed consent, a validated questionnaire was administered to collect data on demographic characteristics, academic level, and utilization patterns of online resources among students. There were 262 participants in the research in which 106(40.5%) were males and 156(59.5%) females Results: There were 262 participants in the research in which 106(40.5%) were males and 156(59.5%) females. There were three age groups identified. In these first group 18-22 years in which most of the students 153(58.4%) were participated, other age group was 23-26 years in which 72(27.5%) students were participated and last group include 27-30 year of age in which 37(14.1%) students were participated. There were five levels of study from which students participated for e learning activities that include 1st to 5th year MBBS in which 23.3% from Ist year, 15.3% from 2nd year, 21.8% from 3rd year, 22.1% from 4th year and 17.6% medical students from 5th year MBBS. Out of 262 medical students 20.2% novice, 41.2% intermediate and 38.5% experienced when relate to the usage of e-learning as shown in table 1. Frequencies, percentages, mean and SD were calculated. P value 0.00 showed significance of the study. Conclusion: This research finds that awareness of e-learning rests in development of skills related to independent learning. E- learning resources are essential for medical education. Enhancing awareness and addressing barriers can optimize utilization, ultimately improving learning outcomes. Keywords: E-learning, medical students, higher education, effective utilization, AI in classroom.